Analisis Kesalahan Mahasiswa Dalam Menyelesaikan Soal Limit Fungsi Berdasarkan Teori Kastolan - Tanjung, July Yanty; Simanjuntak, Rosi Ade Putri; Manullang, Juliana Citra; Turnip, Leonardo; Simanullang, Michael Christian (Mandalika Mathematics and Educations Journal, 2025)
This study aims to identify the causes of errors made by students in solving limit function problems. Limit concepts often present challenges to students due to their complexity, which can lead to confusion. In this research, four students from the Mathematics Education Program at Universitas Negeri Medan served as the subjects, participating in interviews and written tests. They were given limit problems to assess their difficulties in understanding the material. The findings revealed a variety of errors made by the students. Approximately 75% of these errors were due to their inability to organize proper solution steps and incorrect application of formulas. Additionally, 50% of the errors resulted from a lack of understanding of the definition of limits, while 25% were attributed to calculation mistakes or oversights. These results indicate that many students still struggle with the fundamental concepts of limits and the correct methods for solving these problems. To improve student comprehension in this area, it is recommended to implement more interactive and focused teaching methods, enabling them to better grasp the concepts of limits and the appropriate techniques for problem-solving.